National and Ethnic Minorities’ Legal Position in East Central Europe Between 1789 and 1989 - Halász, Iván (Lectures on East Central European Legal History, 2022)
This chapter provides a short history of the legal protection of national minorities in East Central Europe. The region has a relatively long history of legal protection of national and ethnic minorities. This history is connected to the complicated ethnic and social structure across the region because parallel nation- and state-building have been typical for East Central Europe in the last two centuries. The chapter distinguishes three main periods in modern history regarding the issue of minorities. The first legal norms were created in the 19th century. The multilateral international protection of minority rights was established in the interwar period, during the existence of the League of Nations, which played an important role in the realization of this protection. Many countries realized restrictive anti-minority policies during and after the Second World War (mainly in the 1945–1948 years). The introduction of the communist minority policy inspired by the Soviet (Leninist) model in East Central Europe meant an element of stabilization in the sphere of minority issues and the legal protection of minorities. A very important specific feature of the position of East Central European minorities is the dependence on the international politics and position of the great powers. This fact sometimes moderated the minority situation in the region. Despite similar circumstances, conditions, and international challenges, the internal development of the legal protection of minorities underwent a different dynamic process. These differences mainly depended on the internal development of certain states and their societies. The post-war nationalistic repressions were, for example, the most radical in Czechoslovakia and Yugoslavia, which improved the relatively generous minority policy several years later. The post-war situation was more moderate and tolerant in Romania, which implemented a radical anti-minority policy only in the 1970s, when Romania was (relatively) the most independent from pressure from Moscow. A nation-state’s greater independence in international relations (without strong international legal guarantees) was not always good news for the national and ethnic minorities in the East Central European region.KEYWORDS: constitution, East Central Europe, international protection, minorities, state.